Increasing the Growth of Coelogyne rochussenii Orchid Plantlets by administering various concentrations of KH2PO4 and Pyridoxine - Nurhabibah Nurhabibah; Gusti Marlina; Tri Nopsagiarti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Coelogyne is a native Indonesian orchid with relatively large flower sizes and attractive colors. The purpose of this study was to determine the effect of giving concentrations of Potassium Dihydrogen Phosphate (KH2PO4) and Pyridoxine in Murashige And Skoog media on the growth of the Coelogyne Rochussenii De Vriese orchid subculture. The research was conducted at the UPT Tissue Culture Laboratory of Seeds of Food Crops, Horticulture, and Plantation, Riau Province, Jalan Kaharudin Nasution, Kelurahan Simpang Tiga, Kecamatan Bukit Raya, Kota Pekanbaru. The research was conducted for four months, from September to December 2022. The design used in this study was a factorial complete randomized design (CRD) consisting of 2 treatment levels, KH2PO4 and Pyridoxine, with three replications, KH2PO4:160 mgl, 170 mg/l), 180 mg/l), 190 mg/l, and Pyridoxine: 0 ppm 0.0 5 ppm, 0.10 ppm, 0.15 ppm. The results of the study by administering various concentrations of Potassium Dihydrogen Phosphate (KH2PO4) and Pyridoxine did not significantly affect all parameters observed in Murashige and Skoog media on the growth of the Coelogyne Rochussenii De Vriese orchid subculture.